Analysis of Willingness to Pay for Toll Users in Central Java Province - Tri Hermani Wahyuningsih; Setyawan Ary; Syafi’i; Gravitiani Evi (E3S Web of Conferences, 2023)
Transportation infrastructure is a crucial component of national development. Road infrastructure development could lead to increased productivity, global competitiveness, employment opportunities, real sector growth, and reduced poverty. Therefore, this case study aimed to assess the willingness of toll road users in Central Java Province to pay for toll roads and the extent to which the parameters of gender, education, type of vehicle, and occupation affect the willingness to pay. The study also analyzed the variables influencing the toll user’s willingness to pay (WTP). These variables include road conditions, income, age, type of vehicle, frequency of toll users, and travel destinations. Eviews software was used to analyze the economic impact of toll users through logistics regression. Furthermore, Stata software was used to conduct a descriptive analysis of the questionnaire data. The results showed that the frequency of toll users has the greatest impact on willingness to pay, surpassing traffic conditions, type of vehicle, purpose of travel, and travel time. The odds ratio value for the toll user’s frequency was 66.85 [95% CI (13.02-343.07)]. It means that people using toll access more than 15 times are 66.85 times more willing to pay than those using the roads less frequently.